Non-invasive Evaluation of Brain Death Caused by Traumatic Brain Injury by Ultrasound Imaging - Niu, Ningning; Tang, Ying; Hao, Xiaoye; Wang, Jing (Frontiers in Neuroinformatics, 2020)
Objectives To investigate the clinical value of non-invasive ultrasound imaging in the evaluation of brain death caused by traumatic brain injury. Methods Thirty-four patients with acute severe traumatic brain injury were admitted to hospital within 48 h after injury. All patients were monitored intracranial pressure, transcranial Doppler, echocardiography examination, collection intracranial pressure, MCA-Vs, MCA-Vd, MCA-Vm, EF, LVMPI, RVMPI and other indicators, and combined with clinical conditions and other related data for comparative study and statistical analysis. Results The blood flow spectrum was characterized by diastolic retrograde blood flow spectrum pattern and nail waveform spectrum shape when the patient had clinical brain death. For the parameters of transcranial Doppler, there were significant differences in MCA-Vm and PI between clinical brain death group and normal control group (P < 0.05). For the parameters of echocardiography, there were statistically significant differences in EF, LVMPI, and RVMPI between clinical brain death group and normal control group (P < 0.05). Conclusion Non-invasive dynamic monitoring of cerebral hemodynamics and cardiac function parameters in patients with severe craniocerebral injury can provide a high accuracy and reliability for the preliminary diagnosis of brain death in patients with severe craniocerebral injury. It is helpful for early evaluation of prognosis and provides effective monitoring methods and guidance for clinical treatment.